Trichoderma and its role in biological control of plant fungal and nematode disease - Yao, Xin; Guo, Hailin; Zhang, Kaixuan; Zhao, Mengyu; Ruan, Jingjun; Chen, Jie (Frontiers in microbiology, 2023)
Trichoderma is mainly used to control soil-borne diseases as well as some leaf and panicle diseases of various plants. Trichoderma can not only prevent diseases but also promotes plant growth, improves nutrient utilization efficiency, enhances plant resistance, and improves agrochemical pollution environment. Trichoderma spp. also behaves as a safe, low-cost, effective, eco-friendly biocontrol agent for different crop species. In this study, we introduced the biological control mechanism of Trichoderma in plant fungal and nematode disease, including competition, antibiosis, antagonism, and mycoparasitism, as well as the mechanism of promoting plant growth and inducing plant systemic resistance between Trichoderma and plants, and expounded on the application and control effects of Trichoderma in the control of various plant fungal and nematode diseases. From an applicative point of view, establishing a diversified application technology for Trichoderma is an important development direction for its role in the sustainable development of agriculture.